Kepemimpinan Perempuan Aceh - M. Khairunnas; Harmona Daulay; T. Ilham Saladin (PERSPEKTIF, 2022)
The purpose of this study is to find out how the Acehnese paradigm is historically constructed and deconstructed. The problem raised is how the Acehnese people's paradigm towards women's leadership in Aceh and what kind of discourse will help Acehnese women in achieving gender justice. The method in this research is a case study with a qualitative approach. The research subject is the leadership of Acehnese women, and the objects in this research are academics, NGOs (social institutions), community leaders and political figures. The location of this research is in the city of Banda Aceh. Data collection techniques through observation and in-depth interviews. The theory used is the theory of leadership, gender politics and habitus. The results of the study indicate that the implementation of culture and the Islamic sharia system tends to hinder women's movement with the principle of protection. The restrictions on the role of women by patriarchal culture make Acehnese women shackled and receive discriminatory treatment. This inequality between the roles of men and women is one of the structural and cultural barriers that causes individuals in society to not have equal access. The differences in roles, functions, and responsibilities between men and women are the result of social construction and can change according to the times.